Effects of Oral Glucose-Lowering Agents on Gut Microbiota and Microbial Metabolites - Wang, Dongmei; Liu, Jieying; Zhou, Liyuan; Zhang, Qian; Li, Ming; Xiao, Xinhua (Frontiers in Endocrinology, 2022)
Current research and existed facts indicate that type 2 diabetes mellitus (T2DM) is characterized by gut microbiota dysbiosis and disturbed microbial metabolites. Oral glucose-lowering drugs are reported with pleiotropic beneficial effects, including not only decrease in glucose level but also weight loss, anti-hypertension, anti-inflammation and cardiovascular protection, but the underneath mechanisms are still not clear. Evidence can be found that oral glucose-lowering drugs might modify the gut microbiome and thereby alter gastrointestinal metabolites to improve host health. Although the connections among gut microbial communities, microbial metabolites, and T2DM are complex, figuring out how anti-diabetic agents shape the gut microbiome is vital for optimizing the treatment, meaningful for the instruction for probiotic therapy and gut microbiota transplantation in T2DM. In this review, we focused on the literatures in gut microbiota and its metabolite profiles alterations beneficial from oral anti-diabetic drugs, and trying to provide implications for future study in the developing field of these drugs, such as combination therapies, pre- and pro-biotics intervention in T2DM and subjects with pregestational diabetes and gestational diabetes mellitus.